On the creation of small wind power plants in Kazakhstan - Baishagirov, Kh.Zh.; Omarov, B.M. (KU publ., 2019)
The article deals with the data on renewable energy sources in the Republic of Kazakhstan, in particular, on the creation of wind power plants. Here with, there are noted design features of the created small wind power plants. There are identified three stages that arise when creating small wind power plants, as well as a brief description of the corresponding types of work. The role of composite materials in creating new products in mechanical engineering is shown. There are described design features of a composite wind power plant with a diffuser in details. Results of analytical studies and graphs of the air velocity changes inside the diffuser are presented. There are described main points of the manufacturing technology of fiberglass fairings.
Қазақстанда шағын жел энергетикалық құрылғыларды жасау туралы.
О создании малых ветроэнергетических установок в Казахстане
Keywords: wind power plant; composite material; fairing; diffuser; construction; generator